The Role of Catholic Education and Schooling Foundations in Improving the Quality of Schools in South Papua Province - Okto Irianto; Mutiya Oktariani; Henie Poerwandar Asmaningrum (Technium Social Sciences Journal, 2023)
The Merauke Catholic Education and Schooling Foundation is a legal institution that oversees Catholic schools in the ecclesiastical territory of the Merauke Archdiocese. YPPK Merauke manage and provide education in the Merauke District, Boven Digoel District, and Mappi District. YPPK Merauke as a private institution is also responsible for the development of young human resources through education. This study aims to describe the role of YPPK Merauke in improving the quality of its schools in South Papua Province, from the perspective of the foundation’s leadership. This type of research is descriptive qualitative research. Research was conducted at Catholic Education and Schooling Foundations in Merauke during December 2022 to April 2023. The research subjects were 5 informants. data analysis techniques were used which were guided by the Milles and Hubberman method. The research results show that YPPK Merauke has actively contributed to improving the quality of its schools through 6 aspects, namely organizational management, human resources, finance, infrastructure, school management, and partnership management. In conclusion YPPK Merauke plays an important role in improving the quality of schools in South Papua.